Evaluation of Translaryngeal Percutaneous Arytenoid Lateralization (TPAL) in dogs with experimentally created laryngeal paralysis. (April 2018) - Sample, Susannah J.; Hardie, Robert J.; Stein, John; Webb, Julie
Abstract: The aim of this experimental study was to evaluate the effect of Translaryngeal Percutaneous Arytenoid Lateralization (TPAL) in dogs with experimentally created laryngeal paralysis. All dogs (n = 5) underwent bilateral recurrent laryngeal neurectomy before TPAL. Two TPAL suture techniques were evaluated. TPAL-CranialCaudal (TPAL-CC) was performed first, followed 11 to 14 days later by TPAL-DorsalVentral (TPAL-DV). For both techniques, a mattress suture was placed through the arytenoid cartilage via an oral approach. Laryngeal examination was performed before, immediately after, and on days 1, 3 and 7 for both TPAL techniques. Ipsilateral hemiglottic surface area and the degree of laryngeal swelling or reaction to the suture were recorded. Laryngeal tissue was evaluated by histopathology at the end of the study. For both TPAL techniques, hemiglottic surface area was increased immediately after suture placement ( P  < 0.05). At all other times, hemiglottic area was not statistically different from preoperative value ( P  > 0.05). TPAL-DV resulted in less laryngeal swelling compared to TPAL-CC. Histopathology of the arytenoid cartilage surrounding the mattress suture revealed mucosal ulceration and inflammation consistent with the presence of the suture material. Both TPAL techniques were effective at lateralizing the arytenoid cartilage and significantly increasing hemiglottic surface area immediately after suture placement. However, mucosal swelling and loss of tension on the mattress suture lead to a decrease in glottic area within 24 h. Further refinements in suture placement technique are warranted to minimize swelling and improve the duration of arytenoid lateralization prior to clinical application. Highlights: TPAL is intended as a less-invasive alternative to temporary tracheostomy. TPAL is relatively easy to perform and requires no specialized instrumentation. TPAL is effective at lateralizing the arytenoid cartilage and increasing glottic area. Swelling and loss of tension on the suture decreased glottic area within 24 h. Further refinements in technique are warranted to prior to clinical application.